PENGARUH RASIO CAR, NPL, LDR, BOPO, DAN NIM TERHADAP KINERJA BANK UMUM DI INDONESIA - Priyanto Agung Raharjo, Dwi; Setiaji, Bambang; Syamsudin, Syamsudin (Jurnal Manajemen Dayasaing, 2014)
This research is performed on order to test the inï¬‚uence of the variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), BOPO (Operating Expenses / Operating Income), and Net Interest Margin (NIM), to return on Asset (ROA). The sample used in the study were 120 bank in Indonesia in 2010 and 2011. The data analysis technique used is multiple linear regression, t-statistic and F-statistics test with a signiï¬cance level of 5%. During research period show as variable and data research was normal distributed. Based on test, multicolinearity, heterosscedasticity and autocorrelation classic assumption deviation has no founded, this indicate that the available data has fulï¬ll the condition to use multi linear regression model. This result of research show that variable CAR, NIM, and LDR positive signiï¬cant inï¬‚uence toward ROA. Variable NPL and BOPO negative signiï¬cant inï¬‚uence toward ROA. Prediction capability from these seven variable toward ROA is 78,7 % where the balance 21,3% is affected to other factor which was not to be entered to research model.